Utilization Of Methyl Ester Sulfonate As a Surfactant Raw Material in the Scouring, Bleaching and Dyeing Process of Rayon Fabric - Luciana, Luciana; Rizkiah, Riza (Technium Sustainability, 2022)
The use of surfactants from palm oil as a wetting agent can be applied in the textile wet processes. Used cooking oil that has been through esterification and transesterification processes can be used as a raw material for surfactants. During this process, methyl ester sulfonate has been formed as a surfactant raw material. MES surfactant as an active ingredient in detergents has a detergency ability in water with a high hardness level, has a tolerance property to Ca 2+ ions, has a low foaming rate, and has good stability to pH. The purpose of this research is to utilize used cooking oil that has been processed through esterification, transesterification, and sulfonation for the surfactant manufacturing process which will later be used for wet textile processes and to determine the optimum concentration of surfactant produced in the cooking and dyeing process of rayon compared to commercial surfactants (teepol). The experiments carried out were the process of making surfactants from methyl esters into sulfonate methyl esters, through the processes of sulfonation, purification and neutralization. Then, testing the wetting time, absorbency of the fabric and testing the resistance of acid, base, and hardness. Then the surfactant product is applied to the cooking and bleaching processes simultaneously, then the dyeing process is continued with the surfactant as a cloth wetting agent in the dyeing process. Then tested the age and evenness of the dyed fabric color. The results showed that MES surfactant has almost the same properties as a teepol, which holds it hard and not resistant to acids and bases. It has a good wetting ability and can reduce surface tension so that the fabric can absorb water in 23,36 seconds. The optimum conditions were achieved in MES surfactant concentrations using 2 ml / L in the scouring bleaching process (simultaneous) and 2 ml / L in the dyeing process. The color saturation is 25.6148 and the color evenness results in a standard deviation of 0.395.